PELAKSANAAN ITIKAD BAIK MEMORY OF UNDERSTANDINGDALAM PERJANJIAN JOINT VENTUREPERUSAHAAN MODAL ASING - Heru Guntoro (Mimbar Hukum, 2014)
This paper examines the perspective of law in implementation good conviction memory of understanding in joint venture agreement and the result from law implementation memory of understanding in join venture agreement in the supreme court decision. This research is a literary research, the legal matters are analyzed qualitatively using normatif and juridical approach. From research can concludes, implementation from good conviction Memory of Understanding in the joint venture agreement are command of regulation with there are measure and explisit sanction to they who break a promise.